High prevalences of infection with Giardia intestinalis genotype B among children in urban and rural areas of Argentina - Molina, Nora Beatriz (2011)
The protozoan parasite most frequently associated with diarrhoea worldwide is Giardia intestinalis. In 2005, a study was initiated to identify the genotypes of this parasite infecting children in the Argentinian provinces of Buenos Aires, Mendoza and Chaco, and to explore the associations between the genotype detected in a child, the characteristics of the child’s household and the child’s clinical presentation. Overall, 998 children (504 boys and 494 girls) aged between 2–14 years, with or without symptoms, were enrolled. The G. intestinalis in 94 of the 117 stool samples found positive for the parasite by microscopy were successfully genotyped by PCR. Seventy-seven of the children were found to be infected with genotype B only and 14 with genotype AII only, three children being found to have mixed (AII and B) infections. Only genotype B was detected in children from rural areas (P<0·05) and most Giardia detected in children from households with a piped water supply were also of this genotype (P<0·05). The other household characteristics investigated (quality of building, history of flooding, type of sanitation, level of overcrowding, and presence/absence of pet dogs) had no significant effect on the genotype distribution. Children infected with genotype AII were significantly younger than those infected with genotype B (P<0·05) and there was a significant positive association between infection with genotype B and abdominal pain (P<0·05). Diarrhoea was not, however, found to be significantly associated with genotype-AII or genotype-B infection. This is the first published report on the Giardia genotypes circulating in the provinces of Mendoza and Chaco. The results indicate the importance of asymptomatic children in the transmission of Giardia among the young.